TPACK Proficiency among Vocational High School Teachers: Comparative Insights from Public and Private Institutions - Rifana S. S. Inggrid Kawet; I Gede Budi Mahendra; Benyamin Limbong Tampang; Viverdy F.C. Memah (Journal of Education Technology, 2025)
Rapid technological advancement and the demands of Industry 4.0 and Society 5.0 require vocational high school teachers to effectively integrate technology, pedagogy, and content knowledge. However, the implementation of Technological Pedagogical Content Knowledge (TPACK) among vocational teachers in Indonesia remains constrained, particularly due to disparities in institutional support between public and private schools. This study aims to examine the level of TPACK competence among vocational high school teachers and to compare TPACK profiles between public and private institutions. A descriptive quantitative approach was employed involving 62 teachers from eight public and private vocational high schools in Bali and North Sulawesi provinces. Data were collected through Likert-scale questionnaires and interviews, and analyzed using descriptive statistics, multiple linear regression, and independent-samples t-tests. The findings indicate that teachers’ overall TPACK competence falls within a moderate category. Regression analysis reveals that Technological Knowledge (TK) and Content Knowledge (CK) have significant effects on TPACK, while other components do not show partial significance. In addition, a significant difference was found between public and private vocational schools, with teachers in public schools demonstrating higher TPACK competence. This study concludes that sustained professional development and stronger institutional support are essential to enhance vocational teachers’ capacity to integrate technology effectively, particularly in private schools. These findings provide empirical evidence to inform policy and targeted interventions for strengthening TPACK in vocational education contexts.